Breath Tracking System Design with Velostat - Hancilar, Unal; Ayten, Umut Engin (IEEE, 2021)
In this study, a sensor design for the breath tracking system was made using velostat (pressure sensitive foil), neoprene fabric and conductive yarn. As the pressure on it increases, the resistance provided on the velostat decreases, and as the pressure decreases, the resistance value increases. With this feature, it is connected to the body with a belt by taking advantage of the diaphragm movements during breathing and breath detection is provided. With the other sensor types used in the literature, experiments were carried out in 4 different ways as normal breathing, deep breathing, frequent breathing and breath holding. A printed circuit board with a Bluetooth module has been designed for the proposed sensor, which has low cost and ergonomic advantages, and its data has been evaluated on Matlab. 6 different tests were performed with the designed sensor and the results were compared with other methods in the literature according to the evaluation criteria. Sensitivity was 94.63%, specificity 94.25%, precision 95.6%, standard deviation 0.58 breaths/min, root mean square error 1.080 breaths/min, mean absolute error 0.83 and it was shown to be at an acceptable level.
Keywords: Breath; non-invasive respiratory tracking; wearable sensor; sensor design; SENSOR; RESPIRATION; Cell Biology; Engineering